Rebamipide does not interfere with the antitumor effect of radiotherapy or chemotherapy in human oral tumor-bearing nude mice - Masafumi Shibamori; Masayuki Sato; Naoya Uematsu; Takako Nakashima; Asuka Sato; Yoshiya Yamamura; Hiroyuki Sasabe; Ken Umehara; Kazushi Sakurai (Elsevier, 2015)
Recent studies have shown that rebamipide, which suppresses reactive oxygen species, prevents chemoradiotherapy-induced oral mucositis in patients with head and neck cancers. However, anticancer action of radiotherapy and chemotherapy is believed to be partially associated with generation of reactive oxygen species. The aim of this study was to determine whether rebamipide interferes with the antitumor action of radiotherapy and chemotherapy. The effect of rebamipide on tumor cell growth was investigated using a human oral squamous carcinoma cell line, HSC-2, in vitro and in vivo. Rebamipide showed no significant effect on cell or tumor growth in HSC-2 tumor-bearing nude mice. Influences of rebamipide on the antitumor action of radiotherapy and of chemotherapy with cisplatin or docetaxel were investigated using the same animal model. In radiotherapy, the tumor was treated with 2.5 Gy of X-rays for 5 days, and rebamipide (300 mg/kg p.o.) was administered during irradiation periods. In chemotherapy, tumor-bearing mice were treated once with cisplatin (8 mg/kg, i.v.) or docetaxel (15 mg/kg i.v.) and rebamipide (300 mg/kg p.o.) was administered for 5 days following the antitumor drug treatment. Rebamipide did not interfere with the antitumor action of radiotherapy and chemotherapy.